An investigation into the synthesis of cadmium sulfide pigments for a better understanding of their reactivity in artworks. (February 2021) - Ghirardello, Marta; Otero, Vanessa; Comelli, Daniela; Toniolo, Lucia; Dellasega, David; Nessi, Luca; Cantoni, Matteo; Valentini, Gianluca; Nevin, Austin; Melo, Maria João
Abstract: Cadmium yellows are a class of inorganic pigments introduced during the middle of the 19th c. and widely employed by modern painters. Recent research has reported the degradation of cadmium yellow paints in important artworks such as The Scream by Edward Munch, raising questions about its triggering factors. To address this issue, we investigated, for the first time, the historical production methods of Winsor & Newton, one of the leading suppliers of artists' materials. Starting from in-depth documentary research of the Winsor & Newton 19th c. archive database, the foundation for an informed selection of historical preparation methods of these yellow pigments was provided. This allowed us to replicate 19th c. recipes, enabling us to understand better historical synthesis processes and their impact on the properties of cadmium yellow pigments. The pigments prepared, as well as reference pigments, were characterized through surface-sensitive methods in a multi-faceted analytical approach. The results show that pigments synthesized following historical indications present polytype crystal structure and crystal grains and aggregates much smaller than reference pigments. More interestingly, the detection of chlorine ions on particles surface (in the form of Cl bonded to a metal) was possible by X-ray Photoelectron Spectroscopy analysis, allowing its exclusion as an environmental contaminant. Finally, we have observed a strong sensitivity of the photoluminescence emission to pigment crystallite and grain size, an occurrence which may significantly impact on the photo-reactivity of the pigment in artworks. Graphical abstract: Image 1 Highlights: Cadmium sulfide pigments were synthesized following instructions of the Winsor & Newton 19th c. archive database. Synthesized pigments show polytipism, small grains and small aggregates with respect to reference pigments. Chlorine ions, in the form of Cl bonded to a metal, were observed on particles surface of some of the synthesized pigments. The synthesized pigments display an enhancement of the non-radiative decay channels with respect to reference pigments All these properties may significantly impact on the photo-reactivity of the synthetized pigments.